2018
DOI: 10.1093/wbro/lky003
|View full text |Cite
|
Sign up to set email alerts
|

Myth-Busting? Confronting Six Common Perceptions about Unconditional Cash Transfers as a Poverty Reduction Strategy in Africa

Abstract: This paper summarizes evidence on six perceptions associated with cash transfer programming, using eight rigorous evaluations conducted on large-scale government unconditional cash transfers in sub-Saharan Africa under the Transfer Project. Specifically, it investigates if transfers: 1) induce higher spending on alcohol or tobacco; 2) are fully consumed (rather than invested); 3) create dependency (reduce participation in productive activities); 4) increase fertility; 5) lead to negative community-level econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 59 publications
5
41
0
1
Order By: Relevance
“…Over the last decade, social safety nets (SSN) have rapidly expanded on the African continent, becoming a core strategy for addressing poverty and vulnerability, responding to shocks, increasing productivity and investing in human capital. Popularity among governments and other stakeholders has been bolstered by regional evidence showing that SSNs are effective in combating poverty and food insecurity, increasing resilience and agricultural productivity, and improving the education and wellbeing of future generations (Garcia and Moore 2012;Bastagli et al 2016;Handa et al 2018;Hidrobo et al 2018). By 2017, every country on the continent had at least one SSN, while the average country had 15, ranging from two (Republic of Congo and Gabon) to 56 (Burkina Faso) (Beegle, Coudouel, and Monsalve 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, social safety nets (SSN) have rapidly expanded on the African continent, becoming a core strategy for addressing poverty and vulnerability, responding to shocks, increasing productivity and investing in human capital. Popularity among governments and other stakeholders has been bolstered by regional evidence showing that SSNs are effective in combating poverty and food insecurity, increasing resilience and agricultural productivity, and improving the education and wellbeing of future generations (Garcia and Moore 2012;Bastagli et al 2016;Handa et al 2018;Hidrobo et al 2018). By 2017, every country on the continent had at least one SSN, while the average country had 15, ranging from two (Republic of Congo and Gabon) to 56 (Burkina Faso) (Beegle, Coudouel, and Monsalve 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Table 13 summarises the key components of the suite of the six evaluations, in addition to Lesotho, and the main findings regarding children-related expenditure. Although specific programme objectives vary, all programmes were designed with poverty-related objectives, including the improvement of food security, health and education of children, and household resilience to negative shocks (Handa et al 2017). One key component of all programmes reviewed here is the fact that they are unconditional.…”
Section: Comparison With Other Cash Transfer Programmes In Sub-saharamentioning
confidence: 99%
“…Th e claim that social safety nets may represent a work disincentive among beneficiaries has been largely disproven (Banerjee et al 2015a(Banerjee et al , 2015b. Similarly, it has been found that benefi ciaries do not tend to use social transfers to purchase temptation goods, such as alcohol and tobacco, but rather to smooth consumption and raise human capital expenditures (Evans and Popova 2014;Handa et al 2017).…”
Section: Strongly Agreementioning
confidence: 99%